Lifelong learning activities for older adults: a scoping review - de Lima Flauzino, Karina (2022)
The lifelong learning paradigm has become a global phenomenon, having an influence on the political organization of various countries. The aim of this study was to map lifelong learning activities for the older people so to understand how this paradigm has been incorporated into practical actions. The scoping review method was chosen and the literature search was conducted across five databases (Web of Science, Scopus, AgeLine, ERIC and MedLine) in English and between the years of 1972 and 2020. All peer-reviewed papers which presented the conceptual notion of lifelong learning as a central topic to the study, the target audience of older men and women (50+ years old) and which described formal, non-formal and informal educational activities, were included in the present research. A total of 2,083 records were found, of which 309 were selected for the full reading screening; this, in turn, resulted in 38 records included. Most of these studies were published in the last decade (66%), originating in North America (36%) and adopting a qualitative methodological approach (81%). The lifelong learning activities for older people were noticeably more frequent in the non-formal modality (60%), within a university context (46%) and from the perspective of the third generation of the concept (60%). It was concluded that there is an imbalance between lifelong learning activities for the older adults in the formal, non-formal and informal modalities and that the lifelong learning paradigm has been incorporated into practical actions by different conceptual generations.